Mathematical Connection Ability And Students’ Independence in Missouri Mathematics Project E-Learning - Suryono, Wiwik Ariyani; Suyitno, Hardi; Junaedi, Iwan (Unnes Journal of Mathematics Education Research, 2020)
This study aims to (1) investigate the effectiveness of Missouri Mathematics Project e-learning model, (2) find the pola of mathematical connection ability and students’ independence of the eighth grade. This research employed mixed method type referring to the concurrent triangulation design which combined qualitative and quantitative research methods. The subject of this study was the eight-grade students of MTs Taqwal Ilah Semarang academic year 2018/2019. The results show that (1) Missouri Mathematic Project model based e-learning is effective enhancing connection ability (2) Discovered the pola of connection (a) students with high mathematical connection ability can associate the mathematical concept with the previous material, and the other subject or related with real life. (b) students with medium mathematical connection ability can associate mathematical concept with real life, but lack of associate the mathematical concept with the other subject, and some students with medium mathematical connection ability can’t associate the mathematical concept with the other subject. (c) students with low mathematical connection ability can’t associate mathematical concept with real life.